O12 HSV-1 counselling what actually happens in consulting rooms? A qualitative evaluation of practice using mystery shopping in English level 3 GUM clinics. (23rd May 2012) - Munday, L; Foley, E; Lamb, T; Green, J; Evans, C; Barton, SE; Patel, R
Abstract : Background: Guidelines indicate best practice for HSV management and topics that should be covered during counselling. Consultations can be difficult, since many complex issues must be explained carefully, and there is opportunity to confuse HSV-1 and HSV-2. Aims: To evaluate the quality, accuracy and differences in advice given by staff (doctors (D), nurses (N) and health advisors (HA)) in Level 3 sexual health clinics (L3SH) on an initial consultation for HSV-1 infection recently diagnosed elsewhere. To assess whether a professional patient mystery shopping approach provides useful information for L3SH. Methods: A prospective qualitative evaluation of 20 consultations was performed. Clinical leads within each unit gave permission for participation; details of the exact nature or time of visit were not shared. A professional patient visited each unit as a patient new to the area seeking advice for a standard complex scenario –various probes gauged management of different clinical scenarios. Field notes were made immediately following each consultation in the form of a written transcript and audio notes. Anonymised written transcripts were provided to a panel of clinicians to classify overall and specific aspects of care as ACCEPTABLE (A), UNACCEPTABLE (U) or a CAUSE FOR CONCERN. Results: Consultations were supported well with written information (not HSV-1 specific). Staff frequently declined to give prognostic information and some confused HSV-1 and HSV-2 guidance. Although many centres are quick to offer patient-initiated therapy this was virtually always at doses that have been superseded in current guidance. The majority of N-led consultations were A with only limited trends in favour of D-provided consultations. HA did not always provide A consultations. Conclusion: PPMS appears to be feasible for assessing some aspects of L3SH care which may otherwise be difficult to gauge. Some aspects of HSV-1 management are well handled but most units do not provide convenient patient-initiated therapy, or support consultations with disease-specific information.